2015
DOI: 10.1111/1758-5899.12212
|View full text |Cite
|
Sign up to set email alerts
|

Using Data Envelopment Analysis to Address the Challenges of Comparing Health System Efficiency

Abstract: Efficiency is one of the most potent measures of health system performance and is of particular interest to policy makers because it seeks to assess the valued outcomes of a health system in relation to the resources that are sacrificed to achieve those outcomes. However, the production process of the health care system is a complex sequence, and most indicators are only able to capture part of that process; these indicators offer limited scope for analysis. While researchers have previously constructed compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 22 publications
2
53
0
6
Order By: Relevance
“…In the EMR, payment systems are typically fee-for-service systems. In developed countries payments are often based on performance at clinical and organizational levels, increasing efficiency through performance incentives [91, 92]. Strategies to increase hospital efficiency include developing healthcare policies to implement appropriate payment systems, fair tariffs, and meticulous workforce recruitment plans, calculating required bed numbers for each community, making optimal use of hospital beds based on demand, and developing two-way electronic referral systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the EMR, payment systems are typically fee-for-service systems. In developed countries payments are often based on performance at clinical and organizational levels, increasing efficiency through performance incentives [91, 92]. Strategies to increase hospital efficiency include developing healthcare policies to implement appropriate payment systems, fair tariffs, and meticulous workforce recruitment plans, calculating required bed numbers for each community, making optimal use of hospital beds based on demand, and developing two-way electronic referral systems.…”
Section: Discussionmentioning
confidence: 99%
“… 34 35 Standard cross-country efficiency studies are frequently criticised in that measures of health (typically life expectancy and mortality) are highly influenced by factors widely outside the health system. 36 Our approach better withstands this criticism since it is measuring the efficiency of the health system’s ability to produce UHC service goals (a direct relationship) and not good health generally (an indirect relationship).…”
Section: Discussionmentioning
confidence: 99%
“…There is now a good amount of evidence available about the relative levels of efficiency in the health sector of high-income countries [6, 7]. A recent review of the literature and other studies have concluded that there is evidence of widespread inefficiencies in the health sector of several OECD countries that help explain their differences in health attainment [8, 9].…”
Section: Introductionmentioning
confidence: 99%